Effectiveness of Choice Theory Training on Adolescent Girls\' Emotional Intelligence - Fatemeh Zare; Fahimeh Namdarpour (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2020)
Aim and Background: Adolescence is an important period of development in which individuals can acquire the skills, attitudes, and abilities they need in adulthood. It seems that one of the factors that can be effective in dealing with adolescent issues is emotional intelligence. This study aims to investigate the effectiveness of Choice Theory training on emotional intelligence in adolescent girls. Methods and Materials: This is a quasi-experimental study with pretest-posttest control group design. The statistical population consists of thirteen-to-eighteen-year-old adolescent girls in the city of Isfahan. The sample consisted of 32 adolescent girls who were selected by multistage cluster sampling and were randomly and equally assigned to control and experimental groups. The experimental group received Choice Theory training in eight ninety-minute sessions. The control group was placed on the wait list. The Emotional Quotient Inventory test was used for data collection purposes and the data were analyzed using the covariance analysis test. Findings: Results showed that Choice Theory training significantly affected Emotional Intelligence and its components (adaptability, intrapersonal, interpersonal, and general mood) (p<.05). However, it was not significantly effective on stress management. Conclusions: According to the findings, it seems that Choice Theory training can be used to increase the emotional intelligence of adolescent girls in schools. Theoretical and practical implementations will be discussed in this research.